Breaking language barriers in physiotherapy: Ensuring consistent English-to-Arabic translations for better patient care - Almahasees, Reem; Almahasees, Zakaryia (Research Journal in Advanced Humanities, 2025)
This study examines the issues and implications of inconsistent translation of physiotherapy terms from English to Arabic, with a focus on patient comprehension and clinical communication in Jordanian healthcare centers. A qualitative approach was employed in two phases. In the initial phase, 100 physiotherapy words, most of which were contributed by translation students from the Applied Science Private University, were reviewed, and ten words were selected for in-depth thematic analysis due to their inconsistency. These included core physiotherapy fields such as musculoskeletal, cardiopulmonary, pediatric, and sports physiotherapy. Analysis reported a wide range of Arabic equivalents, resulting in incorrect interpretation or obscurity while explaining rehabilitation. Semi-structured interviews were conducted in the second phase with ten licensed physiotherapists working in private and public environments. Inconsistencies in translation experienced by clinicians, clinicians' coping strategies for presenting specialized terms to Arabic-speaking patients, and views on the standardization of physiotherapy terminology were explored. Participants reported that inconsistent language frequently hinders successful patient compliance and education regarding treatment plans. There was consensus in favor of having a unified Arabic physiotherapy glossary of terms to improve clinical accuracy and patient involvement.